Training Oral Communication- Skills using an Avatar - van der Stap, Nanda; van Dongen, Emanuel; van Ginkel, Stan (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Training participants to give quality feedback requires them to receive feedback themselves on the feedback they have given to someone else. Such training is time-consuming and anxiety-inducing. Nevertheless, the reception of feedback is primarily dependent on its perceived quality, therefore training is essential. In the present study, an AI-driven Avatar was used as the recipient of feedback, generating a feedback report concerning the feedback given. 200 participants will train themselves using the Avatar, in which their purported findings on perceived value/usefulness of the training, their competence and confidence will be measured (pre and post) using questionnaires based on IMI scales. Additionally, Learning Analytics will be exploited to measure the number of times students logged in, and the duration of their sessions. The overall results should show the effects of using an Avatar on students’ perceptions and confidence on feedback-giving. A future study may show how this affects students’ professional practice.